Cracks in the Dam: The Quiet Faith of a (Censored) Schoolteacher - Weiss, Aaron (Anthropology of consciousness, 2026)
Based on ethnographic research, this paper describes select views and experiences of a Sufi schoolteacher pressured at work into silence about her interpretation of Islam. At Tafsīr Islamic Academy (TIA), unity was broadly construed as achieved through conformity to mainstream Sunni belief and practice. Salihah, one of its teachers and a practicing Sufi, portrayed unity as an all-encompassing quality of Allah, realizable not through the elimination of external diversity but via annihilation of ego. Her pantheism-inflected interpretation of tawhid (God's oneness), positing God as "the only one that exists," was especially deviant. I frame her mystical beliefs as ideational artifacts that helped tacitly facilitate an altered state of consciousness within the classroom, transforming a potentially fruitless interpersonal conflict into an opportunity for spiritual growth. This supports the more general claim that Salihah was not entirely hindered by silence from practicing her faith at Tafsīr, and may have benefited from it.